2018
DOI: 10.2196/publichealth.9221
|View full text |Cite
|
Sign up to set email alerts
|

Defining Care Patterns and Outcomes Among Persons Living with HIV in Washington, DC: Linkage of Clinical Cohort and Surveillance Data

Abstract: BackgroundTriangulation of data from multiple sources such as clinical cohort and surveillance data can help improve our ability to describe care patterns, service utilization, comorbidities, and ultimately measure and monitor clinical outcomes among persons living with HIV infection.ObjectivesThe objective of this study was to determine whether linkage of clinical cohort data and routinely collected HIV surveillance data would enhance the completeness and accuracy of each database and improve the understandin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…The role of surveillance data in demonstration state programs was of particular interest in this analysis. Findings from prior city- and state-sized studies support the use of surveillance data to identify PLWH most in need of targeted outreach and services and to promote efficient use of resources [ 37 , 38 ]. Surveillance data were found to be particularly helpful when states used them in planning.…”
Section: Discussionmentioning
confidence: 94%
“…The role of surveillance data in demonstration state programs was of particular interest in this analysis. Findings from prior city- and state-sized studies support the use of surveillance data to identify PLWH most in need of targeted outreach and services and to promote efficient use of resources [ 37 , 38 ]. Surveillance data were found to be particularly helpful when states used them in planning.…”
Section: Discussionmentioning
confidence: 94%
“…A recent systematic review found that while viral load and adherence improved during jail or prison, post-release HIV-related outcomes were even worse than before incarceration (Iroh et al, 2015). However, recent developments in community-based HIV surveillance methods show promise for improving HIV care linkage, retention, and reengagement in care (Castel et al, 2018;Enns et al, 2016;Mulatu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…From 2011 to 2014, publicly-insured PWH were less likely to achieve VS; privately-insured PWH had an earlier time to VS; and public insurance was associated with earlier time to virologic failure [9]. Further, PWH concurrently receiving care at three or more clinics were more likely to have public insurance and detectable VL, as well as hypertension, cardiovascular disease, and mental health issues [12]. To further probe these findings, we first analyzed demographic characteristics of DC Cohort participants by insurance type.…”
Section: Introductionmentioning
confidence: 99%